2013
DOI: 10.1111/maq.12013
|View full text |Cite
|
Sign up to set email alerts
|

Aging Respectably by Rejecting Medicalization: Mexican Men's Reasons for Not Using Erectile Dysfunction Drugs

Abstract: As lifestyle drug production and medical interest in geriatrics increase, the medicalization of aging and sexuality have become intertwined. Drugs like Viagra naturalize lifelong performance of phallocentric sex as a marker of healthy aging. Yet despite the ubiquity of medical aids for having "youthful" sex in older age, this article argues that having no or less sex can be a conscious strategy for embodying respectable aging. Based on ethnographic research in a Cuernavaca, Mexico, hospital urology department,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 51 publications
(40 reference statements)
0
28
0
1
Order By: Relevance
“…Myths and stereotypes that deny their unique sense of sexual well-being and the right to express it (McAuliffe, Bauer and Nay 2007;Kirkman, Dickson-Swift and Fox 2015) are compounded in ageism, irrational fears, stereotypical thinking and lack of knowledge. Resultant attitudes and behaviours constitute significant barriers to older people's sexual expression, enjoying sexuality and achieving a sense of self (Snyder and Zweig 2010), which is reinforced by the bio-medicalisation of sexuality and the dominant role of pharmaceuticals in sexual discourse (Wentzell 2013;Marshall 2012;Marshall 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Myths and stereotypes that deny their unique sense of sexual well-being and the right to express it (McAuliffe, Bauer and Nay 2007;Kirkman, Dickson-Swift and Fox 2015) are compounded in ageism, irrational fears, stereotypical thinking and lack of knowledge. Resultant attitudes and behaviours constitute significant barriers to older people's sexual expression, enjoying sexuality and achieving a sense of self (Snyder and Zweig 2010), which is reinforced by the bio-medicalisation of sexuality and the dominant role of pharmaceuticals in sexual discourse (Wentzell 2013;Marshall 2012;Marshall 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Gutmann critically engages with the gender construct of machismo, showing how this gloss stereotypes men as one‐dimensional subjects, overgeneralizing the multidimensional nature of male identities and the complicated ways men engage in intimate relations with their female partners, express emotions, and participate in the lives of their children. Building on Gutmann's critiques of machismo, Emily Wentzell examines the construction of what she describes as “composite masculinities” as men respond to the relatively new, and possibly quintessentially “modern,” diagnosis of erectile dysfunction (ED) (Wentzell , 32) . In the current analysis, we are informed by Gutmann's critical deconstruction of masculinities and by the ways masculinity is coproduced through men's interactions with clinical providers and family members in response to chronic mental illness.…”
Section: Schizophrenia and Gender In Mexicomentioning
confidence: 99%
“…Previous work reported that patients with type 1 diabetes (T1D) were identified before the age of 30 [4] and that the number of young persons with T1D and type 2 diabetes (T2D) were uncontrollably high [5]. Further investigations also reported that sexual disorders, such as erectile dysfunction [6] or retrograde ejaculation [7], were manifested in diabetic individuals and generally resulted in a reduced libido [8]. Although, the decline in reproductive health of male diabetics can be attenuated in patients but the molecular mechanism of metabolic pathways aside glucose transport to the cells, remain undisclosed and obscure [9,10].…”
Section: Introductionmentioning
confidence: 99%